2017
DOI: 10.1159/000479240
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Isotypes for Tumor Immunotherapy

Abstract: Compared to the evolutionary diversity of antibody isotypes, the spectrum of currently approved therapeutic antibodies is biased to the human IgG1 isotype. Detailed studies into the different structures and functions of human isotypes have suggested that other isotypes than IgG1 may be advantageous for specific indications - depending on the complex interplay between the targeted antigen or epitope, the desired mode of action, the pharmacokinetic properties, and the biopharmaceutical considerations. Thus, it m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 51 publications
1
43
0
1
Order By: Relevance
“…[4][5][6] Whilst most of the currently approved clinical monoclonal antibodies are of the IgG isotype, the high avidity of IgM and its effective complement activation and agglutination make IgM an attractive candidate for future immunotherapy. 7 Multimeric IgM exists as either ve (pentamer) or six (hexamer) subunits covalently linked to each other via disulde bridges. 8,9 Each IgM subunit is made of four polypeptide chains, namely two heavy chains containing ve immunoglobulin (Ig) domains (Cm1, Cm2, Cm3, Cm4 and VH), and two light chains comprised of two Ig domains (CL and VL) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Whilst most of the currently approved clinical monoclonal antibodies are of the IgG isotype, the high avidity of IgM and its effective complement activation and agglutination make IgM an attractive candidate for future immunotherapy. 7 Multimeric IgM exists as either ve (pentamer) or six (hexamer) subunits covalently linked to each other via disulde bridges. 8,9 Each IgM subunit is made of four polypeptide chains, namely two heavy chains containing ve immunoglobulin (Ig) domains (Cm1, Cm2, Cm3, Cm4 and VH), and two light chains comprised of two Ig domains (CL and VL) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated that the EGFR antibody of the human IgG2 isotype, panitumumab, mediates ADCC; however, in contrast to IgG1, the mechanism of panitumumab is limited to recruiting myeloid effector cells against EGFR‐positive tumor cells . The IgG2 subclass is predominantly selected for neutralizing antigens or inhibiting receptor‐ligand interactions . When IgG with low effector function but high resistance to acidic conditions is needed, IgG1 LALA or IgG1 N297V may be a better choice, as the disulfide isoforms of IgG2 limit the extent to which quality control is feasible .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the IgG1 isotype is predominantly used in antibody therapy. Kretschmer et al [2] review the potential of alternative human isotypes in therapeutic application. Kellner et al [3] summarize established and emerging Fc engineering strategies, whereas Wirt and colleagues [4] analyze the potential of combining different Fc engineering strategies.…”
Section: Figmentioning
confidence: 99%